Scoping Review on the Effects of Simulation-Based Interventions on Reducing Stigma Toward People with Schizophrenia - Eva-Maria Weiß; Dagmar C. Unz; Frank Schwab (Frontiers in Virtual Reality)
IntroductionSchizophrenia imposes a significant burden on global public health and is associated with pervasive stigmatization, perpetuating misconceptions of danger and incompetence. This review examines the efficacy of simulation interventions in reducing stigmas associated with schizophrenia and fostering empathy towards affected individuals.MethodsA comprehensive literature review spanning from August 2021 to September 2022 identified 14 relevant studies meeting inclusion criteria.ResultsAnalysis revealed a diverse landscape of simulation-based interventions, characterized by variability in methodological rigor, intervention design, and technological modalities. While some studies demonstrated promising outcomes in stigma reduction and empathy enhancement, methodological limitations and inconsistencies underscore the need for cautious interpretation of findings. Furthermore, mixed outcomes in stigma characteristics and empathy development highlight the complexity of intervention effectiveness.DiscussionDespite these challenges, simulation interventions, particularly when integrated with additional components, hold potential in mitigating stigmatization and promoting empathy. Future research should prioritize methodological rigor, comprehensive outcome assessment, and tailored intervention strategies to advance the field of stigma reduction in schizophrenia.